Self-Tuning of Service Priority Parameters for Optimizing Quality of Experience in LTE - Oliver, Pablo; Toril-Genovés, Matías; Luna-Ramírez, Salvador; Garcia Garaluz, Rafael (IEEE Xplore, 2017)
Rising user expectations are changing the way mobile operators manage their networks. In this paper, a self-tuning algorithm for adjusting parameters in a multiservice packet scheduler of a Long-Term Evolution base station is proposed to optimize the overall system Quality of Experience (QoE) based on network performance statistics. For this purpose, the algorithm iteratively changes service priority parameters to reprioritize services so as to make the most of available resources. The proposed algorithm ensures that the best overall system QoE is always reached by analyzing optimality conditions, unlike previous works, which only guarantee a minimum user satisfaction level or aim to balance QoE among services. Method assessment is carried out with a dynamic system-level simulator in a realistic service scenario. Simulation results show that the overall network QoE can be improved up to 35% by tuning service priority parameters.
Keywords: Optimización; Long-Term Evolution; Quality of Experience; Optimization; Re-prioritization; Self-organizing network; Services